Influence Of Socio-Economic Factors On Choice Of Childbirth Place Among Women In Oyigbo, Rivers State, Nigeria - Ngozi Afulenu Obika-Ndiri; Chizoma Millicent Ndikom; Ogochukwu Immaculate Obika (Faculty of Medicine, Universitas Andalas, 2022)
Choices of childbirth places among women may influence the rate of maternal mortality which is still a major challenge especially in developing countries like Nigeria. Some of these choices could be influenced by social and economic factors and the commonest being home birth which increases maternal risks. This study aimed to find out the prevalent socio-economic factors that influence the birthplace choices among the women in a suburban community in Rivers State, Nigeria. The study utilized a descriptive, cross-sectional design. Respondents were selected through simple random sampling. A self-structured questionnaire was used to collect data for the study. The data were analyzed using frequency and percentage for descriptive statistics and chi-square for inferential statistics with the SPSS software at 0.05 level of significance. The result showed that most of the women had secondary education (57.1%) and choose health facility for childbirth (91.4%).There was significant association between distance (x²= 12.69, p= 0.005)and available finance (x²= 10.26, p= 0.016), and educational qualifications (x²= 18.75, p= 0.005)and the choices of childbirth places among the women, but there was no significant association between road access to health facility (x²= 5.47, p= 0.140)and unavailability of skilled birth personnel (x²= 6.23, p= 0.101) and income (x²= 8.38, p= 0.212) and choices of childbirth places among the women. This study has shown that there is influence of some socio-economic factors on the choices women make on childbirth places.